Identification of Potential Key Genes in the Pathogenesis of Chronic Obstructive Pulmonary Disease Through Bioinformatics Analysis - Guan, Qingzhou; Tian, Yange; Zhang, Zhenzhen; Zhang, Lanxi; Zhao, Peng; Li, Jiansheng (Frontiers in Genetics, 2021)
Chronic obstructive pulmonary disease (COPD) is a common respiratory disease with high morbidity and mortality. The etiology of COPD is complex, and the pathogenesis mechanisms remain unclear. In this study, we used the COPD gene expression data of rat and human from our laboratory and Gene Expression Omnibus (GEO) database to identify differentially expressed genes (DEGs) between COPD and normal individuals. Then, protein–protein interaction (PPI) networks were constructed and hub genes were identified. Cytoscape was used to construct the co-expressed network and competitive endogenous RNA (ceRNA) networks. A total of 198 DEGs were identified and PPI network with 144 nodes and 355 edges was constructed. 12 hub genes were identified by cytoHubba plugin in Cytoscape. Among those genes, CCR3, CCL2, COL4A2, VWF, IL1RN, IL2RA and CCL13 were reported to be related with inflammation or immunity, or tissue-specific expression in lung tissue. COL4A2, VWF and IL1RN were verified by GEO dataset GSE76925, and the ceRNA network were constructed with Cytoscape. Moreover, those three genes were consistent in COPD rat model data compared with control data, and all of their dysregulation direction were reversed when the COPD rat model treated with effective-component compatibility of Bufei Yishen formula Ⅲ. In summary, this bioinformatics analysis strategy may be a useful method for elucidating novel mechanism underlying COPD. And we found three key genes that might play a role in COPD pathogenesis and therapy, which deserved to be further studied in the further.